IMPLEMENTASI PRINSIP NATIONAL TREATMENT DALAM KEBIJAKAN BENTUK USAHA INVESTOR ASING DAN DOMESTIK DI INDONESIA - Dian Qobila Belinda; Fivi Faiqotul himmah; Bhim Prakoso (Bajang Institute, 2023)
The main objective of economic development initiatives undertaken by developing countries is to raise and improve the standard of living of their citizens so that they can live like citizens of developed countries. Legal, political and social factors are some of the factors that support the implementation of economic d evelopment. The legal aspect is very important in an effort to create a climate that can encourage economic development and maintain connections in every component and party of economic actors. Investment or investment can be interpreted as the activity of utilizing funds by investing in productive businesses with the hope of obtaining the capital retrieval of the initial funds in the future, so that the owner of funds or capital also gets a number of benefits that will be obtained from investment activities. In the Investment Law, the principle of National Treatment is mentioned in the Explanation of Article 3 Paragraph (1) letter d which reads,